Homosexuality hidden on Cinema of the XX century - Sánchez del Pulgar Legido, Rosa María (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2017)
From the beginning of the XX century in the United States and Europe people lived their homosexuality hidden for fear of the laws that punished it. The cinema represents them in the same way by creating a subculture where homosexuals can be themselves. Classical cinematography and beyond are composed of numerous films loaded with homosexual representations hidden. Interpreted from a ‘queer’ reading we know the thousand ways of suggesting gays and lesbians on the big screen, exposing the true sexual condition of many characters. Latent homosexuality suggests mode without explicitly express it. The films were produced and read in straight key but throughout the film there is a homosexual subtext. Gay statements had to be clear enough but care enough to avoid arousing the suspicion of the censors whonsometimes omitted so many movie scenes that were lacking a logical narrative. It pays attention the presence of gays and lesbians, major or minor characters, which their latent homosexuality is imposing by censorship. The main objective is to understand the reasons of censorship and respond to how they could offer a story with homosexual components without noticing it. The intention is to analyze the content of these films, the evolution of the roles and the meanings have been linked to each of them and find relationships in the latent discourse.